The Impact of Digital Comic Strip in the 4th Grade Young Learners’ Reading Comprehension in Singaraja - Wijaya, Viona Meilly (International Journal of Digital Learning on Languages and Arts (IJODLLA), 2025)
The purpose of this study is to find out the impact of digital comic strip in young learners’ reading comprehension. The setting of this study is in SD Negeri 1 Seririt with the 40 samples of young learners in fourth grade. In this study, post-test and control group only design is applied. The data is analyzed by independent sample t-test in SPSS, the analysis is conduct to compare the post-test result of experimental group and control group in order to find the differences in the mean score of the test. The mean result of the post-test showed there is a significant effect (p < 0.05) in teaching with digital comic strips. The result of the t-test also showed there is a significant effect (p < 0.05). these test result confirmed that digital comic strip is give a significant effect to the students’ reading comprehension rather than teaching with only using conventional teaching media, because teaching with digital comic strips as the instructional media give a better result rather than teaching only with conventional teaching media. It is proven by the result of the post-test using digital comic strip is better than conventional media. This result also evidenced that teaching young learners should be with interactive, creative, interesting teaching media in order to foster enjoyment in the class.